A new combination for the determination of ultratrace cadmium: solid-phase microextraction by stearic acid-coated magnetic nanoparticles prior to batch-type hydride generation atomic absorption spectrometry - Kasa, Nursu Aylin; Akkaya, Erhan; Zaman, Buse Tugba; Cetin, Guelten; Bakirdere, Sezgin (SPRINGER, 2018)
Solid-phase microextraction method based on stearic acid-coated magnetic nanoparticle has been combined with batch-type hydride generation atomic absorption spectrometry (BT-HGAAS) system to determine cadmium at ultratrace levels. After the adsorption of cadmium ions onto stearic acid-coated magnetic nanoparticles, they were easily separated from the aqueous phase by means of a magnet. All the instrumental and experimental parameters such as pH of buffer solution, interaction period, concentration, and volume of NaBH4 were optimized. Under the optimal conditions, limit of quantification (LOQ) and limit of detection (LOD) for the solid-phase microextraction (SPME) based on stearic acid-coated magnetic nanoparticles-BT-HGAAS (SACMNP-BT-HGAAS) method were obtained as 270.8ng/L and 81.7ng/L, respectively. The matrix-matching calibration method was performed in order to improve the accuracy of cadmium quantification in tap water and the recovery results obtained were as follows: 88.568.92 and 97.439.76, for 6.0 and 8.0ng/mL of cadmium-spiked tap water samples, respectively.
Keywords: Cadmium; Magnetic nanoparticles; Stearic acid; Batch-type hydride generation atomic absorption spectrometry; Solid-phase microextraction; PLASMA-MASS SPECTROMETRY; ENVIRONMENTAL-SAMPLES; BIOLOGICAL SAMPLES; TRACE-ELEMENTS; WATER SAMPLES; ICP-MS; EXTRACTION; PRECONCENTRATION; CHROMATOGRAPHY; EXPOSURE; Environmental Sciences & Ecology